Personality Traits as a Predictor of Marital Quality: A Systematic Review - Samsul Ariski; Siti Rohmah Nurhayati (BIRCU, 2021)
This research aimed to analyze journals in order to provide accurately the complete information about personality traits as a predictor of marital quality. All related studies in electronic databases, including Google Scholar, ScienceDirect, Elsevier, and Springer Link, were reviewed based on Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA) method. A total of 215 sorted articles based on PRISMA guidelines resulted 26 articles to review. The findings showed that couples in high neuroticism had lower levels of marital quality. In other side, couples in high conscientiousness were more satisfied with their relationship so that they had higher levels of marital quality. This study could assist practitioners in analyzing personality traits related to the marital quality. Therefore, practitioners could take appropriate treatments to strengthen couple’s marital life.